If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 30 = 11 + -60 Reorder the terms: 30 + 2x = 11 + -60 Combine like terms: 11 + -60 = -49 30 + 2x = -49 Solving 30 + 2x = -49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 2x = -49 + -30 Combine like terms: 30 + -30 = 0 0 + 2x = -49 + -30 2x = -49 + -30 Combine like terms: -49 + -30 = -79 2x = -79 Divide each side by '2'. x = -39.5 Simplifying x = -39.5
| -8.848=-0.2(6.5n-2) | | 13(60)=x(97.5) | | 5(49)=35(x) | | 13+8y=53 | | 36(x)=8(49.5) | | 2x+15+x+20+3x+25=180 | | 25(x-4)=5(20) | | x^2=19.695 | | 0=11a | | 0.5x+1=3 | | Z/13=4 | | 4x+3y-4=0 | | 4(10-x)=100 | | 7x^2-2y^2-42x-16y-17=0 | | 4(x+1)=-2x-18 | | 14.4a-3.5=3.7 | | 11x+9=13x-3 | | 14a-3.5=3.7 | | 1-3(x+5)/2+3x/5=-1 | | 46-5x=112-16x | | 25x+7-7x= | | 2x+30+4x+150=180 | | 9kx^2+6kx+k^2= | | 10(2x+1)= | | -6x+29=47 | | 3r+7+2+r= | | -5x-23=3(3x-3) | | -26=2(x-3) | | 8x+21=x+91 | | 34=2(2x-3) | | (6xy+xy^3)-(3x^3y^2-4xy^3)= | | c-5/9(f-32) |